2001
DOI: 10.3171/spi.2001.95.1.0122
|View full text |Cite
|
Sign up to set email alerts
|

A craniocervical injury—induced syringomyelia caused by central canal dilation secondary to acquired tonsillar herniation

Abstract: ✓ The authors report on a 19-year-old man with an acquired tonsillar herniation caused by a craniocervical junction injury in which serial magnetic resonance (MR) images demonstrated patent and isolated segments of the central canal participating in the dilation and then formation of a cervical syrinx. The patient was involved in a motor vehicle accident; he developed tonsillar herniation as a complication of subarachnoid and epidural hemorrhage, predominantly observed around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Central canal dilation has been noted in autopsy studies of syringomyelic patients [ 33 ] and an ultrastructural analysis of post-traumatic syrinxes revealed ependymal remnants lining portions of the cavity [ 34 ]. Using serial MR imaging, Takamura and colleagues have documented a case of post-traumatic progressive central canal dilation leading to syrinx formation in a young adult [ 35 ], but until now this feature has not been fully appreciated in an experimental model of the disease. In our studies, mild to moderate dilations of the central canal lumen were not associated with gross degeneration of the ependymal and peri-ependymal regions, whereas large aneurysmal dilations of the central canal lumen were consistently associated with a circumferential degeneration of the ependymal and peri-ependymal regions, indicating that gray matter degeneration in chronic SCI is preceded by changes in the ependymal region and/or intraluminal cerebrospinal fluid (CSF) dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Central canal dilation has been noted in autopsy studies of syringomyelic patients [ 33 ] and an ultrastructural analysis of post-traumatic syrinxes revealed ependymal remnants lining portions of the cavity [ 34 ]. Using serial MR imaging, Takamura and colleagues have documented a case of post-traumatic progressive central canal dilation leading to syrinx formation in a young adult [ 35 ], but until now this feature has not been fully appreciated in an experimental model of the disease. In our studies, mild to moderate dilations of the central canal lumen were not associated with gross degeneration of the ependymal and peri-ependymal regions, whereas large aneurysmal dilations of the central canal lumen were consistently associated with a circumferential degeneration of the ependymal and peri-ependymal regions, indicating that gray matter degeneration in chronic SCI is preceded by changes in the ependymal region and/or intraluminal cerebrospinal fluid (CSF) dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…A persistent central canal does not resemble the presyrinx entity clinically or radiographically. 2,11 Takamura, et al, 16 however, reported a single case of a patient with a patent central canal who developed hydrocephalus and an acquired Chiari malformation following a severe head injury; subsequently, progressive symptomatic enlargement of the central canal occurred 2 months postinjury. Craniovertebral decompression resulted in collapse of the syrinx cavity and neurological recovery.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,8) Venous congestion and the swelling of the posterior fossa structures arising from a supratentorial arteriovenous malformation can also cause tonsillar herniation. 6) Mechanism of the deterioration of preexisting Chiari type I malformation secondary to cerebellar hemorrhage is unknown, but the cerebellar hematoma could have displaced the tonsils in the spinal canal into a lower position in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8] improvement after spontaneous disappearance of the hematomas. 5) In the present case, we chose conservative treatment rather than surgical decompression because we thought that the tonsillar herniation would improve after the disappearance of the cerebellar hematoma.…”
Section: Discussionmentioning
confidence: 99%